Optimization of Village Sustainable Development Goals with Creative Tourism in Selumbung Village, Manggis, Karangasem - Ni Luh Putu Ening Permini; Cokorda Putra Indrayana; Cok Gde Agung Kusuma Putra (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2022)
One sector which is the foundation for improving the national economy is tourism. Lack of innovation and creativity causes many tourist destinations to have not differences and uniqueness with other tourist destinations. However, there were many opportunities from villages that can be developed and then integrated with each other in order to support the uniqueness of an area. The types of this research is descriptive qualitative. The research methods used are observation, interview, documentation and internet access. The purpose of this research is to develop community participation so that tourism development will be more effective and efficient because the community will be more responsible for the sustainability of tourism. So the Penta helix Collaboration is needed in realizing village empowerment holistically. So that creative tourism innovation is realized to increase village income.